Risks and benefits of anti-TNF therapy for ulcerative colitis in a patient with autoimmune hepatitis-related cirrhosis: Case report - Dutra, Renata de Medeiros; Pinto, Fernanda Patricia Jeronymo; Craveiro, Marcela Maria Silvino; Baima, Júlio Pinheiro; Hossne, Rogerio Saad; Romeiro, Fernando Gomes; Sassaki, Ligia Yukie (Wolters Kluwer, 2024)
RATIONALE: Ulcerative colitis (UC) is an inflammatory bowel disease (IBD) characterized by continuous inflammation of the colonic mucosa. Autoimmune hepatitis (AIH) is a chronic liver disease characterized by hypergammaglobulinemia, circulating autoantibodies, interface hepatitis, and favorable response to immunosuppression. An association between IBD and AIH is uncommon, and experts have suggested that in patients with overlapping IBD and AIH, the anti-tumor necrosis factor agents can be used. Therefore, this study reports a rare case of a patient with liver cirrhosis due to AIH and UC refractory to conventional treatment and discusses the risks and benefits of using anti-tumor necrosis factor in both conditions. PATIENT CONCERNS: A 28-year-old female presented with symptoms of diarrhea, abdominal pain, asthenia, and inappetence, accompanied by abdominal collateral circulation, anemia, alteration of liver enzymes, and elevation of C-reactive protein levels. DIAGNOSES: The patient underwent a liver biopsy, which was consistent with liver cirrhosis due to AIH. Colonoscopy showed an inflammatory process throughout the colon, compatible with moderately active UC. INTERVENTIONS: The patient received mesalazine, azathioprine, and corticotherapy, with no control of the inflammatory process. Faced with refractoriness to drug treatment and side effects of corticosteroids with an increased risk of severe infection due to cirrhosis, we opted to use infliximab for the treatment of UC. The patient presented with a clinical response and infliximab therapy was maintained. OUTCOMES: Eight months after starting infliximab therapy, the patient developed pneumonia with complications from disseminated intravascular coagulation and died. LESSONS SUBSECTIONS: AIH is a rare cause of elevated transaminase levels in patients with UC. The best treatment to control the 2 conditions should be evaluated with vigilance for the side effects of medications, mainly infections, especially in patients with cirrhosis.